About The Words Meaning the Term "Philosopher" In the Works of Alisher Navoi - Xilola Abdujabborova (Zien Journals, 2022)
This article describes the use of lexical meaning and terminological interpretation of words and concepts that replace the word philosopher and its synonyms in the works of Alisher Navoi from a linguistic point of view, through which the peculiarity of the genius of the thinker is manifested
Keywords: philosophy; philosopher; sage; term